PEGARUH TERAPI ABDOMINAL STRECHING TERHADAP TINGKAT DISMENOREA PADA REMAJA PUTRI SMA NEGERI 11 KOTA JAMBI TAHUN 2022 - Lessy Lovita (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Dysmenorrhea is a menstrual disorder that almost all women experience. The incidence is very large, 50% more than the average woman in the world. Efforts to overcome dysmenorrhea there are two ways, namely pharmacologically such as administration of analgesic drugs and hormonal therapy. And non-pharmacologically is the consumption of healthy food, adequate rest, exercise, warm compresses, dysmenorrhea exercise, consumption of warm chocolate, stretching/stretching. Abdominal stretching which is a muscle stretching exercise, especially in the abdomen which is done for 10-15 minutes. This exercise is given with the aim of increasing muscle strength, endurance and flexibility so that it is expected to reduce menstrual pain. This study is a quantitative research research design pre-experimental one group pre-test post-test aimed at the Effect of Abdominal Stretching Therapy on the Level of Dysmenorrhea in Adolescent Girls at SMA Negeri 11 Jambi City in 2022. This study was conducted in January - July 2022. The population in this study was all teenage girls of SMA Negeri 11 Jambi City in 2022, totaling 325 respondents. The sample in this study used the Lameslow formula with a sample of 31 respondents. Accidental sampling technique of sampling. The statistical test used in this study was the Wilcoxon test with a significance level of 95% (α = 0.05 or 5%). It is said that there is an effect if p_value 0.05 there is no effect if p_value > 0.05.